Feasibility of laparoscopic hysterectomy in stage iv pelvic endometriosis: Our technique and outcomes - Devi Balasubramaniam; Kavitha Yogini Duraisamy; Palanivelu Chinnusamy; Swathi Nethaji; Sangeetha Karunanithi (Wolters Kluwer Medknow Publications, 2020)
Context: The definitive surgical treatment of severe endometriosis remains to be hysterectomy whether done by laparoscopy or laparotomy. Aim: The aim of this study was to assess the feasibility and outcome of laparoscopic hysterectomy in severe pelvic endometriosis. Settings and Design: This retrospective study was carried out in a tertiary center over a period of 5 years (January 2013-December 2017). Subjects and Methods: A total of 70 patients who underwent laparoscopic hysterectomy for severe pelvic endometriosis with a score of more than 40, which was defined by the revised American Fertility Society classification, were included in the study. Feasibility of laparoscopic hysterectomy and other clinical parameters such as operative time, blood loss, recurrence of the disease, and need for postoperative medical treatment was analyzed. Results: The mean age of the patients was 43.2 ± 4.56. Majority of the women (62.8%) had dysmenorrhea as the primary complaint, followed by menorrhagia (21.4%). Intraoperatively rectovaginal septum was involved in 95% of the cases with complete obliteration of the pouch of Douglas in 80% of the cases. The ureter was involved in 34% of the cases. The bladder was densely adherent in 71.4% of the patients. There was no conversion to laparotomy in any of these patients and no visceral injuries. The mean duration of surgery was 3 h. The estimated blood loss ranged from 100 to 500 ml. The duration of hospital stay was 2-5 days. There was no recurrence during follow-up in any of these patients. Conclusions: Laparoscopy in experienced hands is feasible and safe even in difficult cases of Stage IV pelvic endometriosis apart from offering superior results.